Empowerment Status of Rural Women through Self Help Groups (Indian Journal of Extension Education, 2009)
The study was conducted to assess the extent of empowerment of rural women members through SHGs in Satara District in Western Region of Maharashtra State by interviewing 120 rural women from 24 Self Help Groups. It revealed that majority of the respondents after joining SHGs were included in high category of psychological, cultural, social, economical and political empowerment, repectively. Maximum number of respondent belong to moderate category of overall empowerment. Further , study revealed that majority of the respondent had increased their self reliance and self confidence after joining SHGs. More than half of the respondent were empowered to interact with males outside the family. More than two third respondent were socially empowered through access to modern technology, taking self education and participating in community programme. Great majority of respondents were getting freedom to start the business and were getting for economic development. More than two-third respondents became aware about political institution and more than half felt free to participat in active politics after joining SHGs. Due to participation in SHGs there was an overall empowerment of rural women.